Microbiota and diabetes: an evolving relationship. Issue 9 (15th May 2014) - Tilg, Herbert; Moschen, Alexander R
Abstract : The gut microbiota affects numerous biological functions throughout the body and its characterisation has become a major research area in biomedicine. Recent studies have suggested that gut bacteria play a fundamental role in diseases such as obesity, diabetes and cardiovascular disease. Data are accumulating in animal models and humans suggesting that obesity and type 2 diabetes (T2D) are associated with a profound dysbiosis. First human metagenome-wide association studies demonstrated highly significant correlations of specific intestinal bacteria, certain bacterial genes and respective metabolic pathways with T2D. Importantly, especially butyrate-producing bacteria such as Roseburia intestinalis and Faecalibacterium prausnitzii concentrations were lower in T2D subjects. This supports the increasing evidence, that butyrate and other short-chain fatty acids are able to exert profound immunometabolic effects. Endotoxaemia, most likely gut-derived has also been observed in patients with metabolic syndrome and T2D and might play a key role in metabolic inflammation. A further hint towards an association between microbiota and T2D has been derived from studies in pregnancy showing that major gut microbial shifts occurring during pregnancy affect host metabolism. Interestingly, certain antidiabetic drugs such as metformin also interfere with the intestinal microbiota. Specific members of the microbiota such as Akkermansia muciniphila might be decreased in diabetes and when administered to murines exerted antidiabetic effects. Therefore, as a 'gut signature' becomes more evident in T2D, a better understanding of the role of the microbiota in diabetes might provide new aspects regarding its pathophysiological relevance and pave the way for new therapeutic principles.